Molecular cloning of five β-glucosidases from four species of higher termites (Blattodea: termitidae) - Bujang, Nurmastini Sufina; Harrison, Nigel A.; Su, Nan Yao (Entomological Society of America, 2014)
Cellulose is the most abundant polymer in the biosphere, and termites are one of the most important metazoan cellulose processors. Termites are a rich source of digestive enzymes such as endo- β-1,4-glucanases, β-glucosidases, xylanases, amylases, pectinases, and laccases, regardless of whether they are termite derived or of microbiotic origin. Molecular identification of the termite's digestive enzyme is a critical initial step toward using termites as bioresources for industrial applications. Here, we report five β-glucosidase sequences obtained from four species of higher termites (Anoplotermes schwarzi Banks, Macrotermes carbonarius (Hagen), Rhynchotermes bulbinasus Scheffrahn, Sphaerotermes sphaerothorax (Sjoestedt)) with differing nutritional biologies. The deduced amino acid sequences indicated that they were most similar to β-glucosidases in the glycosyl hydrolase family 1 (GHF1). All complete coding sequences are 490 amino acids long and contain conserved motifs involved in substrate binding and catalysis. Each sequence was also predicted to be glycosylated at two sites.